Cooperative Downloading by Multivehicles in Urban VANET - Di Wu; Yingrong Bi; Jie Liang (International Journal of Distributed Sensor Networks)
In VANET (vehicular ad hoc network), RSUs (road side units) have limited coverage and high deployment cost, so they are deployed sparsely in urban area, which leads to blind zone (BZ) between adjacent RSUs, where vehicles cannot connect to Internet by RSUs. In this paper, we study how to use RSUs and vehicles to download big files cooperatively in BZ. In order to choose the cooperative vehicles with minimum total delay, we propose a sequential decision vehicle selection method based on the residual file (SSRF). The method divides the process of selection into several stages and selects cooperative vehicles from the candidates; the decision sequence generated by SSRF determines the set of cooperative vehicles. Simulation and data analysis show that our method is effective in terms of delivered ratio and file delivered delay.